Penerapan Teknik Role Playing dalam Bimbingan Kelompok untuk Meningkatkan Kepercayaan Diri pada Remaja di SMA Kristen Rantepao - Eunike Satodin; Maibo Saludung Patandung; Wulan Dini Manati; Novianti Nensi Liling; Friska Marianty (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to describe the application of role-playing techniques in group guidance to improve self-confidence in adolescents at Rantepao Christian High School. A descriptive qualitative approach was used with eight eleventh-grade students with low self-confidence, identified through initial observations and interviews. Data were collected through in-depth interviews, participant observation during eight group guidance sessions, and documentation such as student reflection journals. Data analysis followed the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results showed that role-playing techniques were effective in improving students' self-confidence, as evidenced by increased active participation, group speaking skills, and positive self-expression post-intervention. Students were initially hesitant and shy, but after role-playing in social scenarios such as presentations and peer interactions, they showed significant behavioral changes. Supporting factors included a supportive group atmosphere and positive feedback from counselors and peers. This study contributes to guidance and counseling practices in Christian schools, emphasizing the importance of experiential methods such as role-playing for adolescents in the North Toraja community. Practical implications are recommended for guidance and counseling teachers to integrate this technique into student self-development programs.